Line Narrowing in the Sulforhodamine B Dye Solution with TiO2 Scattering Center - Chiad, Baha T. (Iraqi Journal of Laser, 2006)
A random laser is a non-conventional laser whose feedback mechanism is based on dissorder-induced light. However, random lasers occur in gain media with numerous scatterers and produce coherent laser emission without any predesigned cavity. The generation of coherent emission from multiple scattering is quite general and its basic principles are shown here using sulforhodamine B-TiO suspensions system. These suspensions were pumped with 337.1 nm pulses from N2 laser and the spectral and temporal behavior of light emitted from the pumped surface was recorded. When we pump power above a certain threshold a dramatic narrowing of the emission line width and a shortening of the emitted pulses were observed. We have experimentally found that in a random laser based scattering, the threshold pumping density decreases with pump energy increased.